Energy Saving Potential for Tun Fatimah Residential College: A Case Study of UTHM Residential College - Hariri, Azian; Hadri, Azmil Asraf (Research Progress in Mechanical and Manufacturing Engineering, 2020)
Inefficiency of energy usage has become main concern among the building owners. To ensure proper energy consumption of the building, it has become a practice to conduct building energy performance study. In Universiti Tun Hussein Onn Malaysia (UTHM), there are many residential colleges for student. Tun Fatimah residential college (KKTF) and Tun Dr Ismail residential college (KKTDI) are located close to each other and both has the same building structure. However, in term of energy consumption, KKTF has higher energy consumption compared to KKTDI. Therefore, a study was carried out to investigate the energy saving potential at KKTF. This study aims to identify energy consumption in KKTF, user behavior, and to identify any potential energy saving that can be applied at KKTF. This study was carried out firstly by identifying characteristics of the building, KKTF electrical bill for one-year, electrical equipment used, and user behavior through field observation and questionnaire. From the result, it is observed that general equipment has highest energy consumption (34%) followed by air conditioning and mechanical ventilation (ACMV) system (32%), and lighting system (31%). Therefore, three type of potential saving method or Energy Conservation Measures (ECMs) were proposed later in this study which focused on no, low/medium and large investment measures. With these proposed measures, KKTF is estimated to reduce the energy consumption by 28% in the future.